Public Sector Employment Regimes : Transformations of the State as an Employer /: Transformations of the State as an Employer. (2015) - Professor, Gottschall, Karin; Kittel, Bernhard; Briken, Kendra; Heuer, Jan-Ocko; Hils, Sylvia; Streb, Sebastian; Tepe, Markus
No abstract available